Development of Simple Control System for a Negative Pressure Wound Therapy Device - Angga Davida; Basari Basari (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2023)
Diabetic ulcers are wounds found on the legs of diabetic patients. Improper treatment opens the risk of complications like sepsis and osteomyelitis. A notable method of treatment is through a Negative Pressure Wound Therapy (NPWT) device. This device helps ulcer recovery by removing exudate, increasing blood flow, and promoting cellular proliferation via negative pressure. The objective of this study is to increase the local content of an affordable and effective method of diabetic ulcer therapy by developing a simple, low-cost NPWT prototype. This was achieved by using an Arduino UNO microcontroller, which included PID controls, an MPXV4115VC6U sensor reading function, an in-built timer, two modes, and an alarm system. The resulting prototype was calibrated before testing to reduce error rates. Testing was conducted using a Gas Flow Analyzer and an ulcer wound phantom. Negative pressure settings of 75, 85, and 125 mmHg were used for testing and were conducted on both modes for 30 minutes each. From these tests, it was found that the prototype could reach the negative pressure thresholds with minimal average error of at most -1.81%. With a wound phantom, the average error was -0.56% and -0.20% for the continuous and intermittent modes respectively. This small variance is negligible because NPWT therapy has a wide range of acceptable negative pressure, namely 60-80 mmHg and 80-125 mmHg, depending on wound type. In conclusion, a simple Arduino UNO-based system can function as an NPWT therapy device to aid diabetic ulcer recovery with minimal error.